2008
DOI: 10.1002/jat.1356
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate‐induced modulation of cellular antioxidant enzyme activities and glutathione level in the J774A.1 cells

Abstract: Dichloroacetate (DCA) is used for different medical and industrial purposes and has been found to be a toxic by-product produced during the process of water chlorination. The DCA effects on superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) activities and glutathione (GSH) level were assessed and correlated with each other and also with cellular viabilities in J774A.1 macrophage cells. A concentration of 24 mm of DCA resulted in time-dependent decreases in cellular viability and glutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The results of this study also differ from those of in vitro studies showing an association between SA production and cellular death induced by DCA and TCA on macrophage cell culture. These differences are clearly related to the toxicokinetic of the compounds in an in vivo , as compared with an in vitro system (3234)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study also differ from those of in vitro studies showing an association between SA production and cellular death induced by DCA and TCA on macrophage cell culture. These differences are clearly related to the toxicokinetic of the compounds in an in vivo , as compared with an in vitro system (3234)…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies on the effects of the compounds in the J774A.1 macrophage cells have also assessed the protective effects of antioxidant enzymes and TNF antibodies against the compounds’-induced SA production (3334). Recent studies have demonstrated the production of phagocytic activation in the peritoneal lavage cells (PLCs) of B6C3F1 male mice, several hours after exposure to single high doses of DCA and TCA (18).…”
Section: Introductionmentioning
confidence: 99%
“…It is also being evaluated for the treatment of cancer [Michelakis et al, 2008;Bonnet et al, 2007]. Unfortunately, however, DCA is toxic [Shroads et al, 2008;Hassoun and Mehta, 2008]. It is taken up by the mitochondria of both normal and abnormal cells, and once located within mitochondrial membranes is routinely metabolized by the mitochondria into oxalic acid, a substance that, like lactic acid, is toxic to many cell types when over-produced, particularly neurons Aicher et al, 1999].…”
Section: Biochemical Transformations Involving Mitochondriamentioning
confidence: 99%
“…Until this time, however, the effect of DCA on type I or type II pneumocytes has not been reported. Type II cells secrete pulmonary surfactant, and, in response to lung damage, proliferate and differentiate into the type I pneumocytes that are responsible for gas exchange [ 31 , 32 ]. Damage to type II pneumocytes is highly detrimental to lung function and, thus, understanding DCA's effects in type II pneumocytes is critical to the evaluation of its toxicological impact.…”
Section: Introductionmentioning
confidence: 99%